Disordered Tin Oxide Films for Thermoelectric Applications: Correlation between Microstructure, Electrical Conductivity and Seebeck Coefficient - V. K. Ksenevich; V. A. Dorosinets; M. A. Samarina; N. A. Poklonski; I. A. Svito; D. V. Adamchuk; G. Abdurakhmanov (Приборы и методы измерений)
The aim of the work was to establish a correlation between structural, electrical and thermoelectric properties of the disordered tin oxide films to study the possibility of their further applications as materials for thermoelectric converters. Disordered multiphase tin oxide films were synthesized by magnetron sputtering of tin onto glass substrates in argon plasma and subsequent two-stage annealing in air. The structural, electrical and thermoelectric properties of the films were varied by changing the temperature at the 2nd stage of annealing in the range of 350–450 °C. It was found that the films synthesized at a temperature of 350 °C during the 2nd stage of annealing procedure have an amorphous structure and are characterized by the highest value of specific electrical conductivity σ ≈ 28.5 S/m. Samples fabricated at temperatures 400 and 450 °C during the 2nd stage of annealing are characterized by polycrystalline multiphase structure with both stoichiometric (SnO, SnO2) and non-stoichiometric (Sn2O3 and Sn3O4) phases of tin oxides in their composition (with prevailing of SnO2 phase for the samples annealed at 450 °C). It was found that these samples are characterized by a higher value of the Seebeck coefficient S (–156 μV/K and –163 μV/K, respectively) compared to the amorphous films, for which the value S = –90 μV/K. It was found that the electrical conductivity of both amorphous and polycrystalline tin oxide films in the temperature range of ≈ 80–300 K can be described within the frame of a model that assumes the activation of electrons from impurity levels in the band gap associated with oxygen vacancies in different charge states. It was demonstrated that for all types of the samples, the Pisarenko’s formula can be applied to evaluate the relationship between the Seebeck coefficient S and the position of the Fermi level EF if the parameter r < –2.